2020
DOI: 10.1097/pcc.0000000000002258
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Practice Related to the Use of High Flow Nasal Cannula in Critically Ill Children

Abstract: Objectives: To determine current management of critically ill children and gather views regarding high flow nasal cannula therapy and to evaluate research priorities for a large prospective randomized controlled trial of noninvasive respiratory support in children. Design: Multinational cross-sectional questionnaire survey conducted in 2018. Setting: The sample included pediatric intensive care physicians in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In addition, this may have a greater impact on PICU bed‐availability during the winter season. To our knowledge, this is one of the first studies assessing the weaning practices from any type of NIV support in the pediatric population, 15 and the first about CPAP and BiPAP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this may have a greater impact on PICU bed‐availability during the winter season. To our knowledge, this is one of the first studies assessing the weaning practices from any type of NIV support in the pediatric population, 15 and the first about CPAP and BiPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Several national and multinational surveys have demonstrated that pediatric intensivists currently select HFNC for initial respiratory care in cases of severe bronchiolitis 18,19 . This popularity among caregivers appears to be associated with the perception of a technique that is easy to implement, with comparable effectiveness and fewer complications than CPAP 20 .…”
Section: Oxygen Low Flow Hfnc (2 L/kg/min) Cpap (7 CM H2o) Niv‐ps Nivmentioning
confidence: 99%
“…In practice, CPAP and HFNC are introduced early in the course of the disease—even as a preemptive measure in some cases—in infants generally not exhausted. While NIV is widely used to treat bronchiolitis, 25 most clinicians, unlike in Delacroix et al's 14 study, consider BiPAP the next step for patients failing with HFNC or CPAP 19 . Failure rates vary widely, from 10% to 50% in the major randomized controlled studies, 1,2,22–24 and depend on multiple factors, the most important probably related to the criteria and delays in defining failure.…”
Section: Oxygen Low Flow Hfnc (2 L/kg/min) Cpap (7 CM H2o) Niv‐ps Nivmentioning
confidence: 99%
See 2 more Smart Citations